2020
DOI: 10.1111/jth.15020
|View full text |Cite
|
Sign up to set email alerts
|

The role of the androgen receptor in prostate cancer‐induced platelet aggregation and platelet‐induced invasion

Abstract: Background: Metastatic prostate cancer progresses from a hormone sensitive androgen receptor expressing phenotype to a hormone insensitive androgen receptor-independent subtype with low overall survival. Human platelets contribute to metastasis via tumor cell-induced platelet aggregation, which in part enhances cancer cell invasion. Given the more aggressive nature of hormone insensitive prostate cancer, we hypothesized that androgen receptor-negative prostate cancer cells exhibit higher platelet aggregation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
2
22
0
1
Order By: Relevance
“…This might be explained by a higher propensity to cloak with other cell types like macrophages or neutrophils. A recent study has shown that prostate cell line models can vary in their ability to induce platelet aggregation which is linked to their androgen receptor expression and this may also explain the reciprocal trends observed between the PC-3 and LNCaP [36] that represent androgen independent and dependent models respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by a higher propensity to cloak with other cell types like macrophages or neutrophils. A recent study has shown that prostate cell line models can vary in their ability to induce platelet aggregation which is linked to their androgen receptor expression and this may also explain the reciprocal trends observed between the PC-3 and LNCaP [36] that represent androgen independent and dependent models respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusively, the loss of androgen receptors in cancer cells accounted for the increased thrombogenicity, due to the enhanced expression of prothrombin. In sharp contrast, androgen receptor-positive prostate cancer cells cannot induce TCIPA ( 40 ). Mitrugno et al.…”
Section: Cancer-associated Thrombosis and Thrombo-inflammationmentioning
confidence: 96%
“…The thrombogenic lesions also increase the risk of TCIPA after surgical intervention ( 39 ). Interestingly, deficiency or inhibition of androgen receptor function in prostate cancer cells could induce TCIPA in vitro ( 40 ). Conclusively, the loss of androgen receptors in cancer cells accounted for the increased thrombogenicity, due to the enhanced expression of prothrombin.…”
Section: Cancer-associated Thrombosis and Thrombo-inflammationmentioning
confidence: 99%
“…The 22RV1 cell line was derived from a xenograft that was serially propagated in mice after castrationinduced regression and relapse of a human prostatic carcinoma xenograft, and its growth is androgen-independent [66]. PC3 and DU145 are human metastatic PCa cells [67,68] without AR expression, and their growth is androgen-independent [69][70][71].…”
Section: Cell Culturementioning
confidence: 99%